INFRINGEMENT OF EMPLOYERS’ PERSONAL RIGHTS IN THE INTERNET - Rogozińska-Mitrut, J. (Wydawnictwo Naukowe IVG, 2021)
In recent years, the issue of protection of personal rights in employment relationships has become increasingly important. On the one hand, the reason for this is the increase of the threat to these goods caused by the employer’s desire to succeed in the conditions of increased competition - employers minimize personal risk, often by excessive and unjustified control over employees, which may lead to a violation of their personal rights.
Keywords: - personal goods; employer; legal protection; confidentiality of information